Cultural Landscape Development Integrated with Rural Revitalization: A Case Study of Songkou Ancient Town - Jing Shen; Rung-Jiun Chou (Land, 2021)
As a form of World Heritage, cultural landscapes have evolved linked with production systems and living space and have become an important topic of rural studies worldwide. This paper attempts to examine the development experiences of local revitalization combined with the cultural landscape in Songkou ancient town, China. Firstly, the rural livelihood-based landscape characteristics of mixing natural and man-made environments are the resources of cultural landscape development. Secondly, community action forms the cultural landscape through a spatial identification process involving place, identity, and heritage. Thirdly, “experience grafting” is a coordinated action for industrial development that has allowed the experience of community revitalization in Taiwan to make an effective contribution to the cultural landscape development of Songkou ancient town. The main findings are as follows: (1) The close connection between man and nature is confirmed from the perspective of landscape cognition and provides farmers with a means of earning a living. Hence, agricultural activities meet the principles of sustainable and organic agriculture by using natural resources responsibly. (2) By considering ecological orchards as cultural landscapes, community actions promote a consensus of local values and an effective way of making a livelihood.